Bathymetric maps from multi-temporal analysis of Sentinel-2 data: the case study of Limassol, Cyprus - E. Evagorou; C. Mettas; A. Agapiou; K. Themistocleous; D. Hadjimitsis (Advances in Geosciences, 2019)
During the last years, various methods and techniques have been used to estimate the seafloor topography with high accuracy. The topography is considered an important component for marine applications since several activities and infrastructures are being carried out at the bottom, column and surface of the sea. In this, study, freely and open distributed optical satellite images were used to obtain bathymetric data for shallow waters, (until 30 m below sea level) based on timeseries analysis of multispectral Sentinel-2 datasets. The ratio transform algorithm was implemented for twelve (12) monthly images covering thus a whole year. The different generated Digital Terrain Models (DTMs) were compared with high resolution LIDAR measurements. The results showed that bathymetry can be obtained from satellite data within a Root Mean Square Error (RMSE) ranging from 1.39 up to 2.56 m while more accurate results were generated during the summer period.